2021
DOI: 10.1161/jaha.120.018526
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Postpartum Cardiac Function and Its Association With Preeclampsia

Abstract: Background Preeclampsia is a prominent risk factor for long‐term development of cardiovascular disease. Although existing studies report a strong correlation between preeclampsia and heart failure, the underlying mechanisms are poorly understood. One possibility is the glycoprotein growth factor activin A. During pregnancy, elevated activin A levels are associated with impaired cardiac global longitudinal strain at 1 year, but whether these changes persist beyond 1 year is not known. We hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…An in vitro study using human umbilical vein endothelial cells (HUVECs) has suggested that activin A up-regulates transcription of endothelial vasoconstrictors such as ET-1 [ 75 ]. Moreover, an elevated activin A level had been reported to be strongly correlated with myocardial dysfunction at 1 year after preeclamptic pregnancy, and a recent follow up study confirmed that the activin A level still remained elevated with impaired cardiac function 10 years after preeclamptic pregnancy, implying its potential use as a tool for monitoring women at risk for postpartum CVD [ 76 , 77 ].…”
Section: Molecular Factors Resulting From Inadequate Uteroplacental Perfusion Leading To Preeclampsiamentioning
confidence: 99%
“…An in vitro study using human umbilical vein endothelial cells (HUVECs) has suggested that activin A up-regulates transcription of endothelial vasoconstrictors such as ET-1 [ 75 ]. Moreover, an elevated activin A level had been reported to be strongly correlated with myocardial dysfunction at 1 year after preeclamptic pregnancy, and a recent follow up study confirmed that the activin A level still remained elevated with impaired cardiac function 10 years after preeclamptic pregnancy, implying its potential use as a tool for monitoring women at risk for postpartum CVD [ 76 , 77 ].…”
Section: Molecular Factors Resulting From Inadequate Uteroplacental Perfusion Leading To Preeclampsiamentioning
confidence: 99%
“…A recent report found that blood pressure variability affects the right ventricle as well [69,70]. Recent data shows that, compared to uncomplicated pregnancies, the ones complicated by preeclampsia affect cardiac function in the long-term, at 10 years post-partum [71]. Moreover, women with early onset preeclampsia showed reduced longterm left ventricular global longitudinal strain associated with a low coronary flow velocity reserve, as a sign of microvascular dysfunction [63] and of higher left ventricular mass [72].…”
Section: Discussionmentioning
confidence: 99%
“…These associations between circulating placental-derived factors and cardiac dysfunction remain significant after multivariable adjustment for clinically relevant confounders, including blood pressure [ 21 , 59 , 60 ]. Importantly, while circulating levels of other placental factors are similar between normal pregnancy and PE [ 59 ], activin A levels are comparable at one year postpartum but significantly elevated at approximately 10 years after a pregnancy complicated by PE [ 20 , 21 ]. These clinical data provide strong evidence of a relationship between plasma activin A and a lifelong risk of cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was found that GLS gradually deteriorates from normotensive pregnancy to gestational hypertension (GH, allegedly without placental compromise) to PE [ 9 , 14 , 15 ], despite comparable blood pressure in these hypertensive groups [ 14 ]. Additionally, GLS remains impaired postpartum even after adjustment for blood pressure and other clinically and biologically relevant variables [ 19 , 20 , 21 ], further supporting a role for placental factors in the development of cardiac dysfunction in PE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation